Rising Skills Premia. You ain't seen nothing yet - Richard Nahuis; H.M. de Groot (Utrecht University, Utrecht School of Economics, Tjalling C. Koopmans Research Institute, 2003)
Increases in inequality between low and high-skilled workers are likely to affect welfare state policies in upcoming decades. Demand for redistribution puts pressure on marginal income-tax rates and other social security measures. We come to this conclusion by confronting expected supply and demand for skill. If demand for skill continues to increase at the pace of the last decades, supply has to keep up its high rate of growth of the last decades too. A priori, the former is plausible, the latter is not. This paper makes this point and sketches the major uncertainties surrounding the underlying trends.
Keywords: 330; Inequality; Policy; Social Security; Cross-country comparison